Aortic root rupture after TAVR in two renal transplant patients on chronic immunosuppressant therapy. Issue 5 (4th November 2014) - Holper, Elizabeth M.; Kim, Rebeca J.; Brooks, Aaron; Mack, Michael
Abstract : Patients on chronic immunosuppressant therapy after renal transplantation have a high rate of in‐hospital mortality and approximately 20% mortality rate per year after conventional valve surgery. While transcatheter aortic valve replacement (TAVR) is an appealing option to consider for such patients, there are not significant outcome data for the procedure in this patient population. We report two cases of aortic root rupture after TAVR in renal transplant patients on chronic immunosuppressant therapy. © 2014 Wiley Periodicals, Inc.